Bone Loss around a Stable, Partly Threaded Hydroxyapatite-Coated Cup: A Prospective Cohort Study Using Rsa and Dxa. Issue 2 (March 2014) - Lazarinis, Stergios; Milbrink, Jan; Mattsson, Per; Mallmin, Hans; Hailer, Nils P.
Study purpose: Aseptic loosening of the acetabular component is the most common reason for revision after primary THA, and periprosthetic demineralisation has been described as a potential cause for this process. The trabeculae-oriented pattern (TOP)-cup is a flat, hydroxyapatite (HA)-coated titanium shell with a threaded rim that was developed in order to minimise periprosthetic bone loss. We hypothesised that this cup provides good primary stability and improves preservation of periprosthetic bone mineral density (BMD). Basic procedures: A prospective cohort study on 30 patients receiving the TOP cup was carried out. Preoperative total hip BMD and postoperative periprosthetic BMD in five periprosthetic regions of interest were investigated by dual energy radiographic absorptiometry (DXA), cup migration was analysed by radiostereometry (RSA), and the Harris hips score (HHS) was determined. Main findings: Mean HHS increased from 49 (24-79) preoperatively to 99 (92-100) after two years. DXA after one year demonstrated substantial BMD loss in the proximal periprosthetic zones 1 (-18%), zone 2 (-16 %) and zone 3 (-9%, all p≤0.001 when compared with baseline BMD determined immediately postoperatively). The bone loss in these regions did not recover after two years. RSA (performed on 16 patients) showed that only very limited micromotion of the implant occurred: Mean cranial migration was 0.01 mm (95% confidence interval (CI): −0.09-0.12) and mean inclination decreased by 0.02° (CI: −0.43-0.39) after two years. conclusion: We conclude that the TOP cup provides good primary stability in the short-term. However, substantial BMD loss in proximal periprosthetic areas indicates that the design of this cup cannot prevent periprosthetic bone loss that has also been observed around other uncemented cups.